2022
DOI: 10.1111/joms.12794
|View full text |Cite
|
Sign up to set email alerts
|

Linking Experience to Intuition and Cognitive Versatility in New Venture Ideation: A Dual‐Process Perspective

Abstract: As many high-profile business leaders purport to make decisions based on gut feelings, a growing number of management scholars are seeking to explain how leaders use intuition in organizational settings. In line with dual-process theories, management scholars argue that the most effective decision makers are cognitively versatile, which means that they are able to 'switch cognitive gears' between intuition and analysis and, more importantly, that they are able to use both types of processing at high levels. Al… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
7
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 17 publications
(12 citation statements)
references
References 119 publications
2
7
0
Order By: Relevance
“…This research contributes to the literature on dual‐process theory in management studies by showing that prior entrepreneurial experience in a given domain enhances the ability of entrepreneurs to make effective use of intuition and analysis in concert, thus enabling them to generate more and better quality (i.e., more innovative) new venture ideas than novices. Baldacchino et al's (2023) findings extend earlier work suggesting that experience facilitates the development and deployment of context‐dependent heuristics that aid decision making (Day and Lord, 1992), effectively turning them into performance‐enhancing managerial capabilities, rather than detrimental rules of thumb (Maitland and Sammartino, 2015), as commonly viewed by heuristics and biases researchers.…”
Section: Extending Complementing and Challenging The Psychological Fo...supporting
confidence: 61%
See 2 more Smart Citations
“…This research contributes to the literature on dual‐process theory in management studies by showing that prior entrepreneurial experience in a given domain enhances the ability of entrepreneurs to make effective use of intuition and analysis in concert, thus enabling them to generate more and better quality (i.e., more innovative) new venture ideas than novices. Baldacchino et al's (2023) findings extend earlier work suggesting that experience facilitates the development and deployment of context‐dependent heuristics that aid decision making (Day and Lord, 1992), effectively turning them into performance‐enhancing managerial capabilities, rather than detrimental rules of thumb (Maitland and Sammartino, 2015), as commonly viewed by heuristics and biases researchers.…”
Section: Extending Complementing and Challenging The Psychological Fo...supporting
confidence: 61%
“…In this special issue, the study of Baldacchino et al (2023) builds on the insights of a prominent parallel‐competitive dual‐process theory — Epstein's cognitive‐experiential self‐theory (Epstein, 1994; Epstein and Pacini, 1999) — in conjunction with the growing literature on managerial and entrepreneurial intuition. Based on a think‐aloud protocol analysis and accompanying survey of 74 technology entrepreneurs, Baldacchino et al (2023) find that, in the process of new venture creation, experienced technology entrepreneurs employ a combination of intuitive and analytical information processing strategies, extensively, in a cognitively versatile manner, switching back and forth as necessary.…”
Section: Extending Complementing and Challenging The Psychological Fo...mentioning
confidence: 99%
See 1 more Smart Citation
“…- [11] Many business leaders, including Elon Musk and Richard Branson, publicly emphasized the importance of intuition in making some of their most fundamental business decisions [12] [13]. Management scholars argue that strategic decision-makingbusiness decisions by managers to achieve and sustain competitive advantage [14] relies on intuitive and rational cognition [8] [15]. Intuitive cognition is fast, automatic, and non-conscious, e.g., jumping away from a car that would hit us [15].…”
Section: Literature Review 21 Intuitive and Rational Decision-makingmentioning
confidence: 99%
“…Scholarly attention has delved into the involvement of intuitive and rational processes in business decisions. Prior research has shown that some business contexts allow combining these tworeferred to as cognitive versatility [8] more easily than others. For example, negotiations between rational, data-driven engineers and intuitive, subjective designers in the design evaluation highlighted alignment challenges [9] [10].…”
Section: Introductionmentioning
confidence: 99%